Effectiveness of full (booster) COVID-19 vaccination against severe outcomes and work absenteeism in hospitalized patients with COVID-19 during the Delta and Omicron waves in Greece. Issue 14 (31st March 2023) - Maltezou, Helena C.; Basoulis, Dimitrios; Bonelis, Konstantinos; Gamaletsou, Maria N.; Giannouchos, Theodoros V.; Karantoni, Eleni; Karapanou, Αmalia; Kounouklas, Konstantinos; Livanou, Maria Effrosyni; Zotou, Maria; Rapti, Vasiliki; Stamou, Panagiota; et al.
Abstract: Aim: We estimated vaccine effectiveness (VE) of full (booster) vaccination against severe outcomes in hospitalized COVID-19 patients during the Delta and Omicron waves. Methods: The study extended from November 15, 2021 to April 17, 2022. Full vaccination was defined as a primary vaccination plus a booster ≥ 6 months later. Results: We studied 1138 patients (mean age: 66.6 years), of whom 826 (72.6 %) had ≥ 1 comorbidity. Of the 1138 patients, 75 (6.6 %) were admitted to intensive care unit (ICU), 64 (5.6 %) received mechanical ventilation, and 172 (15.1 %) died. There were 386 (33.9 %) fully vaccinated, 172 (15.1 %) partially vaccinated, and 580 (51 %) unvaccinated patients. Unvaccinated patients were absent from work for longer periods compared to partially or fully vaccinated patients (mean absence of 20.1 days versus 12.3 and 17.3 days, respectively; p-value = 0.03). Compared to unvaccinated patients, fully vaccinated patients were less likely to be admitted to ICU [adjusted relative risk (ARR: 0.49; 95 % CI: 0.29–0.84)], mechanically ventilated (ARR: 0.43; 95 % CI: 0.23–0.80), and die (ARR: 0.57; 95 % CI: 0.42–0.78), while they were hospitalized for significantly shorter periods (ARR: 0.79; 95 % CI: 0.70–0.89). The adjusted full VE was 48.8 % (95 % CI: 42.7 %-54.9 %) against ICU admission, 55.4 % (95 % CI: 52.0 %-56.2 %) against mechanical ventilation, and 22.6 % (95 % CI: 7.4 %-34.8 %) against death. For patients with ≥ 3 comorbidities, VE was 56.2 % (95 % CI: 43.9 %-67.1 %) against ICU admission, 60.2 % (95 % CI: 53.7 %-65.4 %) against mechanical ventilation, and 43.9 % (95 % CI: 19.9 %-59.7 %) against death. Conclusions: Full (booster) COVID-19 vaccination conferred protection against severe outcomes, prolonged hospitalization, and prolonged work absenteeism.